Pubertal timing, sex hormone levels, and associations between early life adversity and accelerated development amongst 11-year-old children of parents with schizophrenia or bipolar disorder and controls: The Danish high risk and Resilience study via 11 - Mette Falkenberg Krantz; Hanne Frederiksen; Carsten Hjorthøj; Anne Søndergaard; Julie Marie Brandt; Sinnika Birkehøj Rohd; Lotte Veddum; Nanna Lawaetz Steffensen; Christina Bruun Knudsen; Anna Krogh Andreasen; Nicoline Hemager; Birgitte Klee Burton; et al. (Comprehensive Psychoneuroendocrinology, 2023)
Background: Children of parents with severe mental illness have several known risk factors for altered pubertal timing. Pubertal timing is important for children’s physical and emotional development. We aimed to examine pubertal timing and associations between pubertal timing, early life adversity and child problem behavior including psychiatric diagnoses among children of parents with schizophrenia or bipolar disorder and controls. Methods: Self-reported Tanner stage (mean age 11.9, range 10.87–12.67), sex hormone levels, home environment, placement out of home, and problem behavior including psychiatric diagnoses of children at familial high-risk (FHR) of schizophrenia (FHR-SZ), bipolar disorder (FHR-BP) and population-based controls (PBC) were assessed. Results: A total of 465 children participated in the study (Tanner assessment N = 417, sex hormones N = 293). Assessed with self-reported Tanner, no difference in pubertal timing was found between groups (p = 0.09). Hormone levels did not differ between groups except for inhibin B (mean (SD) = 55.86 (29.13) pg/mL for FHR-SZ girls vs 84.98 (47.98) pg/mL) for PBC girls (p < 0.001)) and for follicle stimulating hormone (FSH) (mean (SD) = 5.82 (1.45) U/L for FHR-BP girls vs 4.54 (1.68) U/L for PBC girls (p < 0.001)). FHR children who were placed out of home (17 children, 3.8% of participants) had higher Tanner stages than those living at home (p < 0.001). Timing was not associated with level of problem behavior or psychiatric diagnoses. Conclusions: FHR children did not differ from controls in pubertal timing. Early life adversity assessed as placement out of home may be associated with accelerated pubertal timing among children of parents with schizophrenia or bipolar disorder.